INDECISION CAREER CHOICE PADA SISWA SMK - agung slamet kusmanto; Tyas Martika Anggriana (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2022)
The career process that has been chosen by the individual appropriately is achieved through a good planning process and independent decision making with careful consideration based on an understanding of abilities and interests as well as an introduction to careers that exist in society as a meaningful self-realization. The problem in career decision making can be categorized as an indecision career choice, so that the individual's inability to choose, or make himself to take a certain form of action that will be realized in preparing for and entering a particular job. This research is a type of literature review research by looking for theoretical references that are relevant to the cases or problems found. The results of this study stated that based on the facts in the field, it was found that there were students who had difficulty in making ideal decisions. This condition is influenced by several factors including personality, self-esteem, social support, and career readiness.